Silikotuberkulosis : Kombinasi Penyakit Paru Akibat Paparan Silika yang Meningkatkan Risiko Tuberkulosis pada Pekerja Berisiko - Muthia Verza Mardhiyah; Ikhsan Ikhsan (Lembaga Pengembangan Kinerja Dosen, 2025)
Silicotuberculosis is a complex lung disease, a combination of silicosis and tuberculosis (TB). Silicosis is a disease caused by the inhalation of silica particles, which can lead to pulmonary fibrosis, while TB is an infectious disease caused by Mycobacterium tuberculosis. Long-term exposure to silica dust can cause silicosis and also increase the risk of TB infection, especially in countries with a high TB burden. Workers exposed to silica dust in the mining, construction, and manufacturing industries are among the groups most at risk. The diagnosis of silicotuberculosis is often difficult because the clinical and radiological symptoms of the two diseases often overlap. Symptoms, such as chronic cough, shortness of breath, and chest pain, can be very similar in silicosis and TB, often delaying a correct diagnosis. The pathophysiology of silicotuberculosis involves impaired function of macrophages, immune cells that play a role in fighting infection, and a compromised immune response due to silica exposure. These disruptions facilitate the progression of TB infection, further worsening the patient's health. Primary management of silicotuberculosis includes controlling TB infection with standard anti-tuberculosis drug therapy (OTT) and preventing silica exposure. Preventing occupational exposure to silica dust is crucial to reducing the risk of developing the disease. The prognosis of the disease is greatly influenced by the severity of pulmonary fibrosis and delay in diagnosis. The more severe the fibrosis, the worse the prognosis. Therefore, preventing silica dust exposure, along with routine TB screening for high-risk workers, is crucial to reducing the incidence of silicotuberculosis. Furthermore, education about the risks of the disease is crucial to raise awareness among workers and the general public.